Clinical Characteristics of Pediatric Constipation in Bangladesh - Islam, Fahmida; Rashid, Rafia; Islam, Farhana; Matin, Tahmina Binte; Anisuzzaman, Sheikh (Journal of Current and Advance Medical Research, 2021)
Background: Constipation is a common pediatric problem worldwide. Objective: This study aims to decide the clinical characteristics of pediatric constipation in Bangladesh according to gender and age group. Methodology: All patients with constipation managed at Pediatric Department of Shaheed Tajuddin Ahmad Medical College Hospital, Gajipur, Bangladesh were included between January 2020 to December 2020. Demographic data, clinical characteristics and final diagnosis were recorded. Data were analyzed according to gender and the following age group: infants, pre-school, school age and adolescents. Results: During the study period 64 patients were enrolled. The number (percentage) of patients according to age were the following infants 21(32.8), preschool, 28(43.8), school age 12(18.8) and adolescents 3(4.7). Males made up 35(54.7) of the study population. There was no statistical gender difference in any age group. The most common symptom in all age groups was dry, hard stool. Infrequent defecation was found in almost half of the patients. Fecal incontinence was more common in school aged children compared to pre-school aged children. Abdominal pain was seen in almost 37.5% of the constipated children. Fecal mass in the rectum was the most common physical finding. Conclusion: Clinical characteristics of constipation in children vary according to age group and gender. Older children had less frequent bowel motions, a longer duration of symptoms and a higher prevalence of long-standing constipation complication (fecal incontinence and abdominal pain). Journal of Current and Advance Medical Research, July 2021;8(2):110-113